2023
DOI: 10.1186/s12985-023-02192-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of semen DNA integrity and related parameters with COVID-19 infection: a prospective cohort study

Shuibo Shi,
Hongji Hu,
Jiayao Wang
et al.

Abstract: Background In the context of Corona Virus Disease 2019 (COVID-19) global pandemic, Its impact on male reproductive function should be concerned. Methods Our study is a prospective cohort study that recruited participants infected or uninfected with COVID-19 between December 2022 and March 2023. All laboratory tests and questionnaire data were completed at the First Affiliated Hospital of Nanchang University. A total of 132 participants were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…At the same time, we did not find any studies that took into account different age groups of patients. In men under the age of 35 who had recovered from a coronavirus infection, we observed no significant changes in DNA fragmentation levels, in contrast to the findings of other researchers [21,22]. However, in our sample of older COVID+ patients (>35 years), the proportion of men with increased DNA fragmentation was higher compared to their peers who have not been infected.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At the same time, we did not find any studies that took into account different age groups of patients. In men under the age of 35 who had recovered from a coronavirus infection, we observed no significant changes in DNA fragmentation levels, in contrast to the findings of other researchers [21,22]. However, in our sample of older COVID+ patients (>35 years), the proportion of men with increased DNA fragmentation was higher compared to their peers who have not been infected.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study observed that in patients aged 30 (IQR, 27-34) years, a coronavirus infection in the last 3 months before sample collection resulted in a reduction in sperm concentration, including the percentage of progressively motile sperm, and an increase in DNA fragmentation. Notably, age (under 30 years or older) did not influence DNA fragmentation, in contrast to the significant impact of a prior history of COVID-19 [22].…”
Section: Introductionmentioning
confidence: 67%